A 1-5Ghz, Hybrid Mic Wideband LNA utilizing Microstrip Geometric Structure Variety for Performance Improvement - Rangaiah, Pramod K B; H V, Kumaraswamy (Discoveries in Agriculture and Food Sciences, 2017)
A wideband LNA is design and developed utilizing Hybrid Microwave Integrated Circuit (HMIC) technology for the 1-5GHz bandwidth employing the microstrip line geometric variation. For the performance enhancements in the LNA as for Gain, Noise figure and return loss attributes novel procedures are utilized. The circuit is designed using both lumped elements and distributed components and simulated in AWR microwave office. The LNA design include optimum biasing circuit and microstrip geometric varieties with two distinct renditioned versions. The first version as the geometric structure with radial stubs and second one as linear stubs and whose basic changes were given in the simulation measurements. This paper likewise gives the reasonable strides in insights with respect to hardware implementations. The proposed design especially helpful in the communication systems working under IEEE L and S bands applications. To be more particular it is having more prominent degree application in the radars and defense receiver systems.